Data for: A Morphology-Based Machine Learning Model for Scoring Epithelial-Mesenchymal Plasticity using Organelle Dynamics - Fuxe, Jonas (Karolinska Institutet, 2025)
Project Description:
This project is aimed at modelling dynamic organelle morphology changes in a cellular model of epithelial-mesenchymal transition (EMT). EMT is a developmental process, which is re-activated in cancer and promotes invasion, metastasis and resistance to various therapies.

The repository contains raw microscopy images (.nd2 files) and numerical data outputs of all the experiments performed on a variety of cell lines (breast cancer, lung cancer). Cells were stained with the CellPainting kit. Experiments codes are listed below.

Categories:
Translational and applied bioinformatics; Cellular interactions (incl. adhesion, matrix, cell wall)

Numerical Data Source_wet lab + database (782.78 KB)
(1 excel file with numerical data source for MS experiments; 1 pdf file with WB uncropped membranes images)

Numerical Source Data_all CP experiments (microscopy): (14.47 GB)
- CP015/016/018: NMuMG training set (cellprofiler outputs)
- CP017: NMuMG reversal experiment
- CP019:NMuMG model validation
- CP020: breast cancer cells
- CP_INT_03_Normoxia: A549 Normoxia
- CP_INT_03_Hypoxia: A549 Hypoxia

Images (.ND2 files):
- CP015_nd2 (37.24 GB): NMuMG training set.1
- CP016_nd2 (37.24 GB): NMuMG training set.2
- CP018_nd2 (37.24 GB): NMuMG training set.3
- CP017_nd2 (37.24 GB): NMuMG reversal experiment
- CP019_nd2 (37.24 GB): NMuMG model validation
- CP020_nd2 (37.24 GB): breast cancer cells
- CP_INT_03_Normoxia_nd2 (18.62 GB): A549 Normoxia
- CP_INT_03_Hypoxia_nd2 (18.62 GB): A549 Hypoxia

Image files are in nd2 format, which is Nikon's proprietary format, but can be viewed with open source tools such as ImageJ.

Project Description:
This project is aimed at modelling dynamic organelle morphology changes in a cellular model of epithelial-mesenchymal transition (EMT). EMT is a developmental process, which is re-activated in cancer and promotes invasion, metastasis and resistance to various therapies.

The repository contains raw microscopy images (.nd2 files) and numerical data outputs of all the experiments performed on a variety of cell lines (breast cancer, lung cancer). Cells were stained with the CellPainting kit. Experiments codes are listed below.

Categories:
Translational and applied bioinformatics; Cellular interactions (incl. adhesion, matrix, cell wall)

Numerical Data Source_wet lab + database (782.78 KB)
(1 excel file with numerical data source for MS experiments; 1 pdf file with WB uncropped membranes images)

Numerical Source Data_all CP experiments (microscopy): (14.47 GB)
- CP015/016/018: NMuMG training set (cellprofiler outputs)
- CP017: NMuMG reversal experiment
- CP019:NMuMG model validation
- CP020: breast cancer cells
- CP_INT_03_Normoxia: A549 Normoxia
- CP_INT_03_Hypoxia: A549 Hypoxia

Images (.ND2 files):
- CP015_nd2 (37.24 GB): NMuMG training set.1
- CP016_nd2 (37.24 GB): NMuMG training set.2
- CP018_nd2 (37.24 GB): NMuMG training set.3
- CP017_nd2 (37.24 GB): NMuMG reversal experiment
- CP019_nd2 (37.24 GB): NMuMG model validation
- CP020_nd2 (37.24 GB): breast cancer cells
- CP_INT_03_Normoxia_nd2 (18.62 GB): A549 Normoxia
- CP_INT_03_Hypoxia_nd2 (18.62 GB): A549 Hypoxia

Image files are in nd2 format, which is Nikon's proprietary format, but can be viewed with open source tools such as ImageJ.
Data för: A Morphology-Based Machine Learning Model for Scoring Epithelial-Mesenchymal Plasticity using Organelle Dynamics
Keywords: Organelle Shape; Organellform; Epithelial-Mesenchymal Transition; Epitelial mesenkymövergång; Triple Negative Breast Neoplasms; Trippelnegativa brösttumörer; Cell Plasticity; Cellplasticitet; TNBC - Triple-negative breast cancer; trippelnegativ bröstcancer; Cell and Molecular Biology; Cell- och molekylärbiologi; Medical Bioinformatics and Systems Biology; Medicinsk bioinformatik och systembiologi; Basic Cancer Research; Basal cancerforskning